2022
DOI: 10.1055/a-1897-6121
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sodium-Glucose Cotransporter-2 Inhibitors on Plasma Adiponectin in Patients with Type 2 Diabetes: A Meta-Analysis of Randomized Controlled Trials

Abstract: The influence of sodium-glucose cotransporter-2 (SGLT-2) inhibitors on plasma adiponectin remains not comprehensively evaluated. We performed a meta-analysis to systematically evaluate the effect of SGLT2 inhibitors on plasma level of adiponectin in patients with type 2 diabetes mellitus (T2DM). Randomized controlled trials comparing SGLT-2 inhibitors with non-active controls on plasma adiponectin in T2DM patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…19 Furthermore, in a Taiwanese database study of patients with T2D, ALT reduction from baseline was also significantly greater in patients receiving an SGLT2i than in those receiving a DPP4i (mean difference: -4.0 IU/L; P < .001), with a similar HbA1c reduction between the groups. 20 These results may be explained by the SGLT2i-specific effects, including increased gluconeogenesis and hepatic glucose production, 21 adiponectin [22][23][24] and hepatic β-oxidation. 25 SGLT2is inhibit hepatocyte death and attenuation of abnormal oxidative and inflammatory responses, 26 and may contribute to maintaining or improving albumin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…19 Furthermore, in a Taiwanese database study of patients with T2D, ALT reduction from baseline was also significantly greater in patients receiving an SGLT2i than in those receiving a DPP4i (mean difference: -4.0 IU/L; P < .001), with a similar HbA1c reduction between the groups. 20 These results may be explained by the SGLT2i-specific effects, including increased gluconeogenesis and hepatic glucose production, 21 adiponectin [22][23][24] and hepatic β-oxidation. 25 SGLT2is inhibit hepatocyte death and attenuation of abnormal oxidative and inflammatory responses, 26 and may contribute to maintaining or improving albumin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Ингибиторы НГЛТ-2 повышают уровень адипонектина в плазме у пациентов СД 2. При этом прирост адипонектина являлся более значительным у пациентов с индексом массы тела (ИМТ) <30 кг/м 2 [84].…”
Section: медикаментозная терапия нажбпunclassified
“…Another widely used group of preparations in the treatment of type 2 diabetes is sodium glucose-like transporter 2 inhibitors (SGLT-2). The meta-analysis dedicated to reviewing the influence of sodium–glucose cotransporter-2 inhibitors on plasma adiponectin levels revealed significantly increased plasma adiponectin in type 2 diabetic patients administered tofogliflozin, luseogliflozin, and ipragliflozin, but not dapagliflozin [ 145 ]. In another study, dapagliflozin was shown to downregulate circulating leptin levels in patients with type 2 diabetes and class 3 obesity during a 1-year administration [ 146 ].…”
Section: Adipokines In Clinical Trialsmentioning
confidence: 99%